Peran Pemerintah Dalam Penanganan Stunting Pada Balita Di Kelurahan Alai Kecamatan Ungar - Dea Ayu Fitria (Pubmedia Social Sciences and Humanities, 2024)
Abstrak: Stunting is still a common nutritional problem in many regions. Stunting has a long-term impact as it can jeopardize the quality of future talent. Children who suffer from stunting are more susceptible to disease and are at risk of developing degenerative diseases as adults. Therefore, the role of the village government in the prevention and control of stunting is very important. The purpose of this study was to determine the role of the government in tackling stunting in Alai Village, Ungar District. The methodology used in this research is qualitative, using primary data from interviews with midwives at UPT Puskesmas Ungar and secondary data from several research journals.